EFFECT OF CONCENTRATION KNO₃ AND DURATION OF SOAKING ON THE GERMINATION OF SUGAR PALM (Arenga pinnata (Wurmb.) Merr.) SEEDS - Kristian Yoko Lasut; Arthur Pinaria; Jeane Raintung (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the effect of KNO3 concentration and immersion time on seeds, to support the development of palm oil seed procurement which requires proper seed coat dormancy breaking techniques. The process of hydrolysis of the lignin layer on the palm kernel shell can be degraded through medical and physical treatments. Soaking palm seeds in this study was treated with potassium nitrate (KNO3). concentration of potassium nitrate (KNO3), the need for immersion as independent (independent variable) while the dependent variable (dependent variable) is the strength of palm seeds. Seed dormancy was broken by treatment with several concentrations of potassium nitrate used, namely 0%, 1%, 1.5%, 2% and 2.5%. Treatment The immersion time is for 12, 18 and 24 hours. This study used a completely randomized design (CRD) method which was composed of two factors, namely the first factor K (KNO3 concentration) consisting of K0 = 0% KNO3, K1 = 1% KNO3, K2 = 1.5% KNO3, K3 = 2% KNO3, K4 2.5% KNO3, and the second factor K (Immersion time) consisted of P0 = 0 hours, P1 = 12 hours, P2 = 18 hours, P3 = 24 hours. Palm seed coats that were treated with kalium nitrate concentration experienced dormancy breaking which was indicated by the peeling of the palm seed coat. The results  showed that the rate of exfoliation of palm seed coats on soaking was about 0-12 hours at a concentration of 1% potassium nitrate. Earlier than the immersion time at an average of 12-18 hours and an average of 18-36 hours. Concentrations of KNO3 1%, 1.5% and 2.5% with an immersion time of 0-12 hours got the highest results from all parameters observed , namely se     germination 43-45%, vigor index 2.57%. The highest average length of the plumule was obtained at the average treatment concentration of 1% potassium nitrate at zero (0) hours (K1P0) immersion time with a length of 2.4 cm plumule/palm seed and the average treatment concentration of potassium nitrate 2.5% at soaking time 0- 12 hours and (K4P0) with a plumule length of 2.3 cm/aren palm.Key words : Sugar palm, dormancy, percentage of germination, potassium nitrate concentration and soakingAbstrakPenelitian ini bertujuan untuk mengetahui pengaruh kosentrasi  KNO3 dan lama perendaman terhadap  benih aren, untuk mendukung pengembangan pengadaan benih tanaman aren yang maksimal perlu adanya teknik pematahan dormansi kulit biji yang tepat. Perendaman biji aren pada penelitian ini yaitu dengan perlakuan dengan kalium nitrat (KNO3). Konsentrasi kalium nitrat (KNO3), lamanya perendaman sebagai variabel bebas (independent variable) sedangkan variabel terikat (dependent variable) adalah vigor biji aren.  Pematahan dormansi biji aren dilakukan dengan perlakuan beberapa konsentrasi kalium nitrat yang digunakan adalah 0%, 1%, 1,5%, 2% dan 2,5%. Perlakuan Lama perendaman adalah selama 12, 18 dan 24 jam. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) yang disusun dengan pola faktorial dengan dua faktor , yaitu faktor pertama K (konsentrasi (KNO3) terdiri dari K0 = 0% KNO3,  K1 = 1% KNO3,  K2 = 1,5% KNO3,  K3 = 2% KNO3, K4 2,5% KNO3,   dan faktor kedua K (Lama perendaman) terdiri dari P0 = 0 jam, P1 = 12 jam, P2 = 18 jam, P3 = 24 jam. Kulit biji aren yang diberi perlakuan konsentrasi kalium nitrat mengalami pematahan dormansi yang ditandai dengan pengelupasan kulit biji aren. Hasil penelitian didapatkan bahwa laju pengelupasan kulit biji aren pada perendaman dengan rataan sekitar 0-12 jam pada konsentrasi kalium nitrat 1%. Lebih awal  dibandingkan dengan lama perendaman pada rataan  12-18 jam maupun rataan 18-36 jam. Konsentrasi kalium nitrat 1%, 1,5% dan 2,5% dengan lama perendaman 0-12 jam mendapatkan hasil tertinggi dari semua parameter amatan yaitu kecambah benih 43-45%,  indeks vigor 2,57 %. Rataan panjang plumula tertinggi dihasilkan pada rataan perlakuan konsentrasi kalium nitrat 1% pada waktu perendaman nol (0) jam (K1P0) dengan panjang plumula 2.4 cm/biji aren dan  dan rataan perlakuan konsentrasi kalium nitrat 2,5% pada waktu perendaman 0-12 jam dan  (K4P0) dengan panjang plumula 2.3 cm/biji aren.Kata kunci : biji aren, kalium nitrat (KNO3), dormansi, perendaman